Pertumbuhan Selada (Lactuca sativa L.) pada Pemberian Pupuk Organik Cair dari Buah Pepaya dan Komposisi Media Tanam yang Berbeda - Sity Nurfadilah Ramadhany; Sofyan -; Andi Herwati (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2023)
Lettuce has a fairly large market opportunity, both to meet the needs of the domestic and international markets. High demand for both domestic and foreign markets makes this horticultural commodity have high economic value. The aim of this study was to determine the growth of lettuce (Lactuca sativa L.) when given liquid organic fertilizer from papaya fruit and the composition of several types of planting media. This research was conducted from May to July 2022 in Batulotong Hamlet, Pucak Village, Tompobulu District, Maros Regency. This research method uses a factorial design with the RAK basic design consisting of two factors. The first factor in the form of giving liquid organic fertilizer from papaya fruit consists of four levels, namely: control, 100mL/liter, 150 mL/liter, 200mL/liter and the second factor is the comparison of planting media which consists of three levels, namely: soil, soil+compost, soil + compost + husk charcoal. The results showed that a dose of 150 mL of liquid organic fertilizer from papaya fruit had a significant effect on the growth of leaf length, leaf width and number of leaves. While the composition of the planting medium soil + compost + roasted husks and soil + compost had a very significant effect on the growth of leaf width and leaf length in lettuce plants. The interaction of giving liquid organic fertilizer from papaya fruit at a dose of 150 mL/liter and the composition of the planting medium soil + compost + husk charcoal has a significant effect on leaf width